Dual Topology of Dirac Electron Transport and Photogalvanic Effect in Low‐Dimensional Topological Insulator Superlattices. Issue 9 (18th January 2023) - Xue, Hao‐pu; Sun, Rui; Yang, Xu; Comstock, Andrew; Liu, Yangrui; Ge, Binghui; Liu, Jia‐nan; Wei, Yan‐sheng; Yang, Qing‐lin; Gai, Xue‐song; Gong, Zi‐zhao; Xie, Zong‐kai; et al.
Abstract: Dual topological insulators, simultaneously protected by time‐reversal symmetry and crystalline symmetry, open great opportunities to explore different symmetry‐protected metallic surface states. However, the conventional dual topological states located on different facets hinder integration into planar opto‐electronic/spintronic devices. Here, dual topological superlattices (TSLs) Bi2 Se3 ‐(Bi2 /Bi2 Se3 ) N with limited stacking layer number N are constructed. Angle‐resolved photoelectron emission spectra of the TSLs identify the coexistence and adjustment of dual topological surface states on Bi2 Se3 facet. The existence and tunability of spin‐polarized dual‐topological bands with N on Bi2 Se3 facet result in an unconventionally weak antilocalization effect (WAL) with variable WAL coefficient α (maximum close to 3/2) from quantum transport experiments. Most importantly, it is identified that the spin‐polarized surface electrons from dual topological bands exhibit circularly and linearly polarized photogalvanic effect (CPGE and LPGE). It is anticipated that the stacked dual‐topology and stacking layer number controlled bands evolution provide a platform for realizing intrinsic CPGE and LPGE. The results show that the surface electronic structure of the dual TSLs is highly tunable and well‐regulated for quantum transport and photoexcitation, which shed light on engineering for opto‐electronic/spintronic applications. Abstract : The stacking layer number‐dependent electron structure, quantum properties, and circularly (linearly) polarized photogalvanic effect are assessed in the low‐dimensional dual topological superlattices (TSLs) (Bi2 Se3 )‐(Bi2 /Bi2 Se3 ) N . The results show that the surface electronic structure of the dual TSLs is highly tunable and well‐regulated for quantum transport and photoexcitation, which shed light on engineering for opto‐electronic/spintronic applications.